Flexure Revisited: Strength of Singly Reinforced Beams- A Simple Approach - Khalel, Raid I.; Mohammed, Nisreen S; Shukur, Sameh B.T.; Sarsam, Kaiss F. (Nahrain University College of Engineering Journal, 2015)
181 singly reinforced beam tests available from the literature are investigated to obtain two flexural design methods-one simple proposal and an alternative one that takes into account the influence of rising flexural reinforcement ratio on design. The simple proposal takes significantly less time to apply compared to the alternative one. The former leads to only 0.5% greater COV than the latter. These design methods are compared with four code methods (ACI 318M-11, 318M-99, BS and NZ codes).Based on the ratio of ( being the calculated moment resistance), the two proposal methods give relatively low coefficient of variation (COV) values: 15.9% for the simple method and 15.4% for the alternative method. These compare to COV values of 17.5%, 15.9%, 15.6% and 15.7% for the ACI 318M-11, ACI 318M-99, BS and NZ methods, respectively.One major advantage of the simple design method (Constant value of ? = 0.85) is that all 181 tests lead to safe prediction.